The relationship between moral intelligence and emotional intelligence with life satisfaction - Valielahi, Samaneh; sharbaf, Hamidreza Aghamohamadian (Opción, 2019)
The objective of this research studied the relationship between moral intelligence and emotional intelligence with life satisfaction among the students of Islamic Azad University. The questionnaire was with the simple random sampling method. Sample volume was calculated 200 by Cochran formula. The reliability coefficient of questionnaires was evaluated using Cronbach’s alpha coefficient that was obtained 0.9, 0.78, and 0.85. The obtained results from the research showed the significant relationship between moral intelligence, emotional intelligence, and life satisfaction. In addition, the results of regression analysis by entering method showed that the moral intelligence and emotional intelligence variables predict life satisfaction.